Spatio-temporal impact of climate variability on crop production of Potohar Region, Pakistan (1990-2017) - Miandad, Muhammad; Ansar, Aiman; Rahman, Ghani; Munawar, Saira; Dawood, Muhammad (Ecological Questions, 2025)
Climate variability is a major challenge for humanity, especially in agricultural countries, like Pakistan. Crop production in Pakistan is particularly vulnerable to climate variability. The current research addresses the Spatio-Temporal impact of climate variability on crop production using the Mann-Kendall trend model (MKTM) within the Potohar region, Pakistan. The trends in temperature and resulting changes in rainfall patterns and crops production in this region have a strong relationship with temperature changes, as the agriculture of the Potohar region depends solely on rainfall. There are no alternative means of cultivation in the area so agriculture depends only on the amount and duration of rainfall. To conduct this study, metrological data was collected from the Pakistan Meteorological Department for the three meteorological stations located in the Potohar region. ArcGIS software was used to analyze the satellite images from four different times to observe changes in vegetation cover during this period. Normalize difference vegetation index (NDVI) and Soil adjusted vegetation index (SAVI) from Landsat 5 and 8 were used to assess the levels of vegetation and soil moisture. The MKTM method was applied to demonstrate the fluctuations in annual temperature and rainfall. Rainfall data showed a decrease in annual rainfall and rise in temperature in Rawalpindi and Chakwal districts. The Mann Kendall trend model indicated that there is no significant trend detected in both rainfall and temperature data. The combination of indices identified periods where drought is affecting cultivation. The results showed that significant changes occurred in vegetation cover, with image classification showed the low vegetation cover in recent years. The analysis further explains that the observed deviation in climate data is attributed to the climate variability in this region. Weather factors such as air temperature, humidity, and soil temperature also support the normal growth of crops, ensuring normal crop yields. However, significant changes in rainfall and temperature will affect crop yield in the future.